The association between polymorphisms in the MRPL4 and TNF-α genes and susceptibility to allergic rhinitis. - Xin Wei (Public Library of Science (PLoS), 2013)
Background Allergic rhinitis (AR) is a chronic inflammatory disease of the nasal mucosa, involving a complex interaction between genetic and environmental factors. Evidence suggests that polymorphisms in the gene coding for mitochondrial ribosomal protein L4 (MRPL4), located in close proximity to intercellular adhesion molecule-1 (ICAM-1) gene on chromosome location 19p13.2, may influence the risk factor for the development of AR. Objective The aim of our study was to investigate any association between AR susceptibility and polymorphisms in ICAM-1 gene, as well as associations between AR risk and polymorphisms in MRPL4, nuclear factor-kappaB (NF-κB) and tumor necrosis factor alpha(TNF-α) genes, associated with ICAM-1 expression. Methods A cohort of 414 patients with AR and 293 healthy controls was enrolled from the Han Chinese population in Beijing, China. Blood was drawn for DNA extraction and total serum immunoglobulin E (IgE). A total of 14 single nucleotide polymorphisms (SNPs) in ICAM-1, NF-κB, TNF-α, and MRPL4 genes were selected using the CHB genotyping data from the International Haplotype Mapping (HapMap) and assessed for differences in frequencies of the alleles and genotypes between the AR patients and control subjects. Results TNF-α SNP rs1799964 and MRPL4 SNP rs11668618 were found to occur in significantly greater frequencies in the AR group compared to control group. There were no significant associations between SNPs in NF-κB, ICAM-1 and AR. The SNP-SNP interaction information analysis further indicated that there were no synergistic effects among the selected sets of polymorphisms. Conclusions Our results suggest a strong association between AR risk and polymorphisms of MRPL4 and TNF-α genes in Han Chinese population.